Photocatalytic dehydrogenation of formic acid promoted by a superior PdAg@g-C3N4 Mott–Schottky heterojunction. Issue 5 (18th January 2019) - Liu, Hu; Liu, Xinyang; Yang, Weiwei; Shen, Mengqi; Geng, Shuo; Yu, Chao; Shen, Bo; Yu, Yongsheng
Abstract : The superior PdAg@g-C3 N4 Mott–Schottky heterojunction exhibits boosting dehydrogenation photocatalysis of formic acid (TOF = 420 h −1 ) without any additive under visible light ( λ > 400 nm) at room temperature. Abstract : Herein, we report the production of a superior Mott–Schottky heterojunction that is based on PdAg nanowires (NWs) that grow in situ on graphitic carbon nitride (g-C3 N4 ). Due to the strong Mott–Schottky effect between PdAg NWs and g-C3 N4, the heterojunction enhances the photocatalytic dehydrogenation of formic acid (FA) (TOF = 420 h −1 ) without additives and under visible light ( λ > 400 nm) at 25 °C, which is the best value among all heterogeneous catalysts reported for the photocatalytic dehydrogenation of FA. The H2 production rate is almost constant under the current reaction conditions. Detailed studies reveal that a favorable charge transfer from g-C3 N4 and Ag to Pd makes Pd electron-rich, which enhances the catalytic activity and stability of the heterojunction for the photocatalytic dehydrogenation of FA under visible light. Our studies open up a new route to the design of a metal–semiconductor heterojunction for visible light-driven photocatalytic dehydrogenation of FA.